1999
DOI: 10.1111/j.1540-8159.1999.tb00386.x
|View full text |Cite
|
Sign up to set email alerts
|

Tachycardia Induced Electrical Remodeling of the Atria and the Autonomic Nervous System in Goats

Abstract: Atrial fibrillation (AF) shortens the atrial effective refractory period (AERP). To investigate the role of the autonomic nervous system during this so-called electrical remodeling of the atria (ERA) and during recovery from ERA we analyzed heart rate variability (HRV). In 12 goats atrioventricular (300:150 beats/min) pacing was performed for 24 hours, interrupted at 4, 8, 16, and 24 hours for recording of 500 atrial (AA) intervals during sinus rhythm and measurement of the AERP(430ms) at 7.4 +/- 0.6 sites. Af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 35 publications
1
32
1
Order By: Relevance
“…All patients had long durations of AF; thus, by present understanding, electrical remodeling would be expected to be "complete" (4,13). The degree of spectral power shift to 0.125 Hz with controlled respiration was variable.…”
Section: Preserved Dynamic Electrophysiological Changes In Chronic Afmentioning
confidence: 99%
“…All patients had long durations of AF; thus, by present understanding, electrical remodeling would be expected to be "complete" (4,13). The degree of spectral power shift to 0.125 Hz with controlled respiration was variable.…”
Section: Preserved Dynamic Electrophysiological Changes In Chronic Afmentioning
confidence: 99%
“…[8][9][10][11] Although electrical remodeling is considered to occur even in clinical cases, little is known about this phenomenon, mainly because of the technical limitation in measuring the atrial effective refractory period (ERP). Measurement of ERP using premature stimulus via a catheter is the standard method, but it is invasive and it is impossible to evaluate the ERP during AF.…”
Section: Spectral Analysis Of Atrial Fibrillation Waves In Surface Ecgmentioning
confidence: 99%
“…Although several experimental reports documented the shortening of atrial ERP under continuous rapid atrial activation, i.e., AF, [8][9][10][11] other studies reported no change in ERP in heart failure. Li et al studied the effect of rapid atrial pacing on atrial ERP in heart failure, and reported that the atrial ERP and wavelength were not affected by rapid pacing, whereas they were significantly shortened by rapid pacing in patients without heart failure.…”
Section: Dysfunction and Atrial Electrophysiological Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][5][6][7] This phenomenon leads to the shortening of the wavelength and results in the promotion of both the initiation and maintenance of AF. Electrical remodeling is considered to contribute to the PAF in clinical cases.…”
Section: Electrical Remodeling In Clinical Paf Patientsmentioning
confidence: 99%